Worse prognosis in women, compared with men, after thrombolysis: An individual patient data pooling study of Asian acute stroke registries. Issue 7 (October 2021) - Wang, Xia; Carcel, Cheryl; Wang, Ruigang; Li, Jingwei; Bae, Hee-Joon; Wang, Yilong; Wang, Anxin; Wang, Yongjun; Toyoda, Kazunori; Sui, Yi; Lee, Tsong-Hai; Navarro, Jose C; et al.
Background and purpose: To examine sex differences in disease profiles and short-term outcomes after acute ischemic stroke treated with recombinant tissue plasminogen activator. Methods: Eight national and regional stroke registries contributed individual participant data from mainland China, Japan, Philippines, Singapore, South Korea and Taiwan in 2005–2018. The primary outcome was ordinal-modified Rankin scale at 90 days. Key safety outcome was symptomatic intracerebral hemorrhage (sICH). Results: Of 4453 patients included in the analyses, 1692 (36.3%) were women who were older, more likely to have a more severe neurological deficit, history of hypertension and atrial fibrillation, and a cardioembolic stroke compared to men. Women were more likely than men to have unfavorable shift of modified Rankin scale (fully adjusted odds ratio) (women vs. men) 1.14, 95% confidence interval 1.02–1.28). There was no significant sex difference for death 1.05 (0.84–1.31) or sICH (1.17, 0.89–1.54). Women were more likely to have unfavorable functional outcome with increasing age (P = 0.022 for interaction). In the age groups 70–80 and ≥80 years, women had a worse functional outcome compared to men (1.22, 1.02–1.47 and 1.43, and 1.06–1.92, respectively). Conclusion: In this pooled data from Asian acute stroke registries, women had poorer prognosis than men after receiving recombinant tissue plasminogen activator for acute ischemic stroke, which worsened with age. Women older than 70 appear to have a worse outcome than men which could be explained by greater stroke severity, more AF, and cardioembolic stroke.